A Comparison of Multiparametric Methods for the Interpretation of Solvent-Dependent Chemical Processes - Caroli-Rezende, M; Aliaga-Vidal, C; Aliaga-Vidal, C; Rojas-Montecinos, P; Dominguez-Caru, M (Elsevier B.V., 2020)
Kamlet-Abraham-Taft (KAT) s and Catalán s multiparametric methods for the interpretation of solvent-dependent chemical processes were compared by application to seven probes with solvent-dependent spectroscopic properties recorded in a variety of solvents. Regression analyses of the data obtained from the literature or in the present work allowed a comparison of the two methods, not only from the quality of the fitting of the calculated vs. experimental values for each probe, but also from the interpretation of the solvent effects in terms of the sign and magnitude of the regression coefficients. In general, Catalán s parameters proved superior to KAT s in the interpretation of solvent effects by means of their multiparametric approach. © 2020 Elsevier B.V.
Keywords: Solvent-dependent processes; Multiparametric regression analysis; Kamlet-Abraham-Taft s parameters; Catalan s parameters